2016
DOI: 10.1007/s40653-016-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse and Aggression in Adolescent Girls Involved in Child Welfare: The Role of Depression and Posttraumatic Stress

Abstract: This study investigated the relationship between histories of childhood abuse and aggressive behaviors among adolescent girls involved in child welfare, and determined whether symptoms of post-traumatic stress and depression mediated this relationship. Participants were 237 girls ages 12–19 years. Overall, results indicated 89 % of the adolescents endorsed at least one aggressive behavior towards others. Specifically, 72.0 % engaged in physical aggression, 78.5 % engaged in non-physical aggression, and 51.5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Our first hypothesis that adolescents' lifetime sexual and emotional abuse reported at age 12 would be positively associated with greater PTSS at 12 was supported and in line with previous findings (Auslander et al, ; Hébert et al, ; Yoon et al, ). Contrary to our expectation, physical abuse was not associated with PTSS.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our first hypothesis that adolescents' lifetime sexual and emotional abuse reported at age 12 would be positively associated with greater PTSS at 12 was supported and in line with previous findings (Auslander et al, ; Hébert et al, ; Yoon et al, ). Contrary to our expectation, physical abuse was not associated with PTSS.…”
Section: Discussionsupporting
confidence: 89%
“…Research demonstrates that adolescents who are physically, sexually, and emotionally abused commonly develop PTSS (Auslander, et al, ; Finkelhor et al, ; Kolko et al, ; Lansford et al, ; Sugaya et al, ; Weierich & Nock, ; Yoon, Kobulsky, Yoon, & Kim, ). PTSS include dissociation, anger, irritability, depression, anxiety, and sleep disturbances (Briere, ; van der Kolk, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that the positive moral personality of college students were significantly negatively correlated with anti-social behaviors (e.g., violation, addiction, and attack tendencies; Zhang, 2012). In the developmental period of moral personality, as a childhood experience, childhood psychological abuse was closely related to individual personality characteristics (Gabalda et al, 2009;Martinotti et al, 2009;Conger et al, 2010;Auslander et al, 2016). Studies have shown that psychological abuse was negatively related to extroversion, and individuals who experienced more psychological abuse showed high levels of neuroticism, impulsion, and other negative personality tendencies (Li et al, 2017).…”
Section: Moral Personality As a Mediatormentioning
confidence: 99%
“…Our results also show that students reporting the experience of physical and/ or psychological abuse scored significantly higher in the self-reported measure of aggressive and antisocial traits, overt aggression and norm-breaking behavior, than those not reporting these negative experiences. These results may be explained by the "cycle of violence theory" (Widom, 1989a), which suggests that exposure to abuse in childhood increases the risk of engaging in violent criminal offenses or aggressive behavior in adolescence (Widom, 1989b), and by the fact that the experience of childhood abuse may be heavily involved in a developmental pathway leading to the possible onset of post-traumatic stress disorder and depression (Powers et al, 2015;Wielaard et al, 2018), consequently increasing future levels of aggressive and antisocial behaviors (Auslander et al, 2016;Kendra, Bell, & Guimond, 2012). However, the connection between childhood abuse and adolescent aggression has also been explained by social learning theory hypotheses suggesting that aggression may be a learned behavior through direct or observed violent interactions (Burton, Miller, & Shill, 2002).…”
Section: Discussionmentioning
confidence: 99%